Seed treatment with aminobutyric acids improve carrot seed germination and vigor under thermal stress conditions - Anjos Neto, Antônio Pereira dos (2019)
Carrots are plants adapted to different growing conditions, becoming one of the most cultivated vegetables in the world. In Brazil, it has been cultivated both in winter and summer, but extreme weather can make farmers face problems related to seed germination and plant early development, resulting in the reduction of stand and yield in the productive systems. In the vegetative stage, severe thermal stress can result in retarded growth, chlorosis and leaf necrosis, senescence and even vegetable death. At the cellular level, heat stress can lead to membrane damage, protein denaturation, inactivation of mitochondrial and chloroplast enzymes, impaired protein and carbohydrate synthesis, protein degradation, new protein synthesis, and inhibited carbon metabolism. Making crops tolerants to environmental stress are challenges faced by classical breeding and transgenic approaches and different methods are routinely experimented and applied to enhance the productivity and stress tolerance of crops. One of the simplest ways of giving tolerance to sensitive plant species involves the use of biomolecules with regulatory or stimulating roles in stressed plants, the biostimulants. Biostimulants are defined as substances that contain compounds as microorganisms, microbial inoculants, humic acids, fulvic acids, protein hydrolysates, amino acids, and seaweed extracts that stimulate natural process of plant growth. Some non-protein amino acids, such as γ-aminobutyric acid (GABA), β-aminobutyric acid (BABA) have been commonly studied by the ability of confering tolerance to abiotic stress. With this, the objective of this study was to evaluate the application of a film coating in carrot seeds composed with different rates of GABA and BABA and evaluate it effect on seed germination, emergence and vigor under heat and cold stress.